Nitrogen turnover and N2O/N2 ratio of three contrasting tropical soils amended with biochar - Fungo, B.; Chen, Z.; Butterbach-Bahl, Klaus; Lehmannn, J.; Saiz, Gustavo; Braojos, V.; Kolar, A.; Rittl, T.F.; Tenywa, M.M.; Kalbitz, K.; Neufeldt, H.; Dannenmann, Michael (Elsevier, 2019)
Biochar has been reported to reduce emission of nitrous oxide (N2O) from soils, but the mechanisms responsible remain fragmentary. For example, it is unclear how biochar effects on N2O emissions are mediated through biochar effects on soil gross N turnover rates. Hence, we conducted an incubation study with three contrasting agricultural soils from Kenya (an Acrisol cultivated for 10-years (Acrisol10); an Acrisol cultivated for over 100-years (Acrisol100); a Ferralsol cultivated for over 100 years (Ferralsol)). The soils were amended with biochar at either 2% or 4% w/w. The 15N pool dilution technique was used to quantify gross N mineralization and nitrification and microbial consumption of extractable N over a 20-day incubation period at 25 °C and 70% water holding capacity of the soil, accompanied by N2O emissions measurements. Direct measurements of N2 emissions were conducted using the helium gas flow soil core method. N2O emissions varied across soils with higher emissions in Acrisols than in Ferralsols. Addition of 2% biochar reduced N2O emissions in all soils by 53 to 78% with no significant further reduction induced by addition at 4%. Biochar effects on soil nitrate concentrations were highly variable across soils, ranging from a reduction, no effect and an increase. Biochar addition stimulated gross N mineralization in Acrisol-10 and Acrisol-100 soils at both addition rates with no effect observed for the Ferralsol. In contrast, gross nitrification was stimulated in only one soil but only at a 4% application rate. Also, biochar effects on increased NH4+ immobilization and NO3-consumption strongly varied across the three investigated soils. The variable and bidirectional biochar effects on gross N turnover in conjunction with the unambiguous and consistent reduction of N2O emissions suggested that the inhibiting effect of biochar on soil N2O emission seemed to be decoupled from gross microbial N turnover processes. With biochar application, N2 emissions were about an order of magnitude higher for Acrisol-10 soils compared to Acrisol-100 and Ferralsol-100 soils. Our N2O and N2 flux data thus support an explanation of direct promotion of gross N2O reduction by biochar rather than effects on soil extractable N dynamics. Effects of biochar on soil extractable N and gross N turnover, however, might be highly variable across different soils as found here for three typical agricultural soils of Kenya.